Efeito da poluição do igarapé do Quarenta sobre a expressão gênica e da contaminação por cobre sobre o comportamento e o desenvolvimento larvário, dos anuros Rhinella granulosa e Scinax ruber - Sá, Jorge Felipe Oliveira Franco de (Instituto Nacional de Pesquisas da Amazônia - INPA, 2015)
Populations of anurans have declined and extinctions have been recorded over the last years, most of them related to environmental pollution, changes of land use and emerging diseases. Streams with black water characteristics cross the city of Manaus; however, in recent decades, the population and industries have used them as a sewer system, thereby altering their original chemical composition. The main goal of this study was to evaluate the effect of the pollution occurring in these streams on the anuran of the Amazon, Rhinella granulosa and Scinax ruber. We evaluated the effects of pollutants found in these streams on the evolution of egg to adult stage. We analyzed, under laboratory conditions, the effects of copper, a pollutant found in many streams, on larvae behavior and development of these species, using acute (LC50 test) and chronic tests. For Scinax ruber adults we used the gene expression of the hepatocytes as a tool for physiological analysis, in order to understand the negative effects of a long exposure to pollutants found on the banks of a contaminated city stream (Igarapé do Quarenta). LC50 at 96 h of Rhinella granulosa Gosner 25, Scinax ruber Gosner 25 and Scinax ruber eggs in black water of the Amazon contaminated with copper were 23.48±1.8, 36.37±5.1 and 50.02±3.6 μg/L, respectively. The Biotic Ligand Model (BLM) was used to predict the LC50 values that, based on the results, can be considered a promising tool for these tropical species and water conditions. The Gosner stage 19-21 (related to the appearance of external gills) is the most vulnerable stage and the egg stage is the most resistant, in relation to copper pollution. The sublethal concentration of 30 μg/L of copper (82.5% of LC50 – 96h) had no effect on length, duration of the larvae period, growth rate and body weight of Scinax ruber tadpoles, even when they were exposed for long period of time. Long lasting exposure to contaminants found on the banks of the Igarapé do Quarenta induced, in the liver of Scinax ruber adult males, an increase in the expression of genes involved in oxidation-reduction processes and an increase of 197.7 times in the expression of ERGIC3 gene, 54.7 times the IGF1R gene, and 60.7 times the PDCD6IP in relation to control. These genes are related to growth, viability, migration, colony formation and invasiveness of tumor cells. There was also an increase of 54.7 times in the expression of FANCM gene relative to control. This gene codifies the FANCM protein, involved in DNA damage repair system. The pollutants found in the city creeks can cause serious damage animals health that inhabit these areas, leading them to an early death and thereby reducing the size of local populations. Even the animals that survived to adulthood have to deal with constraints and biological damage caused by their environment.
Keywords: Anfíbios; Ecotoxicologia; Expressão gênica